A Decline in the Quality of Debate? The Evolution of Cognitive Complexity in Swiss Parliamentary Debates on Immigration (1968–2014). Issue 4 (24th September 2015) - Wyss, Dominik; Beste, Simon; Bächtiger, André
Abstract: This article explores the evolution of debate quality in the Swiss parliament. Focusing on immigration debates, we employ a psychological construct—cognitive complexity (CC)—which captures both epistemic and accommodative dimensions of political argumentation. We find a decrease in CC in parliamentary immigration debates over time, but this decrease was driven by the rise of the SVP (Swiss People's Party). However, there was almost no "spillover" of this new communication style to other parties. Moreover, we also find a constant difference between the Ständerat and the Nationalrat, with the former scoring higher on CC and thus asserting its role as a "chambre de réflexion" in immigration debates. Our diachronic focus on the quality of political debate takes a novel perspective on the dynamics of consensus democracy as well as on elite political culture. While our results indicate that the rise of the SVP has transformed the traditional consensual and deliberative pattern of Swiss policy‐making style into one which is geared towards less accommodation and a higher simplicity of political talk, there is still remarkable resilience against this new style of political interaction.